Soil Erosion - Chaturvedi, M. D. (Indian Forester, 1953)
1. In the wake of the post-war reconstruction schemes, attention has come to be focussed on soil erosion as a major problem affecting land economy. The matter is to be viewed from different angles on cultivated and waste lands. On the former, soil conservation measures yield direct, quick and tangible results. The farmer is with and not against us. On wastelands unfit for cultivation, however, the problem takes on a different complexion. These tracts are regarded as no-man's lands. They are subjected to the worst conceivable maltreatment which spells wholesale destruction of vegetative cover. The imposition of the least little restriction on the improvident practices adopted by the peasants is objected to, opposed and made a grievance of. Attempts made in the Kulu valley, Kumaun, Chota Nagpur, Yamuna ravines, Nilgiris, to preserve a soil cover have made little, if any, headway. The problem of soil conservation in such areas is more a social than a technical problem. What is required is not research in determining the technique of soil conservation measures, but devising ways and means to enforce legislative measures to afford such areas protection against domestic animals. 2. Insistence on detailed surveys of the magnitude of the problem will only delay matters. By far the best method of tackling this problem is for the Centre to organize closely knitted demonstration centres throughout the land, - centres which States may replicate and emulate. As an earnest of their co-operation in the matter, the States should be asked to contribute 50 per cent of the total cost involved in the establishment of these centres. 3. The administrative organization proposed to be set up at the Centre for the purpose consists of a Director of Soil Conservation attached to the Board of Forestry, somewhat on the model of the Vice-Chairman of the Indian Council of Agricultural Research.